Modelling annual and orbital variations in the scintillation of the relativistic binary PSR J1141−6545. Issue 3 (8th March 2019) - Reardon, D J; Coles, W A; Hobbs, G; Ord, S; Kerr, M; Bailes, M; Bhat, N D R; Venkatraman Krishnan, V
ABSTRACT: We have observed the relativistic binary pulsar PSR J1141−6545 over a period of ∼6 yr using the Parkes 64 m radio telescope, with a focus on modelling the diffractive intensity scintillations to improve the accuracy of the astrometric timing model. The long-term scintillation, which shows orbital and annual variations, allows us to measure parameters that are difficult to measure with pulsar timing alone. These include: the orbital inclination i, the longitude of the ascending node Ω, and the pulsar system transverse velocity. We use the annual variations to resolve the previous ambiguity in the sense of the inclination angle. Using the correct sense, and a prior probability distribution given by a constraint from pulsar timing ( i = 73 ± 3°), we find Ω = 24.8 ± 1.8° and we estimate the pulsar distance to be D=10^+4_-3 kpc. This then gives us an estimate of this pulsar's proper motion of μα cos δ = 2.9 ± 1.0 mas yr −1 in right ascension and μδ = 1.8 ± 0.6 mas yr −1 in declination. Finally, we obtain measurements of the spatial structure of the interstellar electron-density fluctuations, including: the spatial scale and anisotropy of the diffraction pattern, the distribution of scattering material along the line of sight, and spatial variation in the strength of turbulence from epoch to epoch. We find that the scattering is dominated by a thin screen at a distance of (0.724 ± 0.008) D, with an anisotropy axial ratio A r = 2.14 ± 0.11.